2009
DOI: 10.1097/cad.0b013e32832f4e6f
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of cellular organelles in human liver-derived hepatoma G2 cells induced by adriamycin

Abstract: Adriamycin (ADM) is a commonly used chemotherapeutic drug in the treatment of hepatocellular carcinoma. However, the mechanisms involved in ADM-induced cell death and the molecular basis of ADM resistance are still unclear. To observe the early events that occurred in hepatoma cells in response to ADM, we investigated the alterations of morphology and subcellular distributions of cellular organelles in human liver-derived hepatoma G2 (HepG2) cells after ADM treatment. HepG2 cells were exposed to different dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Since changes in Golgi morphology have been reported to occur during apoptosis (Chiu et al, 2002; Jung et al, 2006; Lane et al, 2002; Mancini et al, 2000; Qian and Yang, 2009), we examined whether DNA-damage-induced Golgi dispersal occurs as a consequence of apoptosis. Although treatment with CPT caused a significant increase in the number of apoptotic cells (Figures 2C and 2D), still only a small fraction of cells became apoptotic (1.74% ± 0.08% [mean ± SEM] positive for cleaved caspase-3 (CCasp-3), coinciding with other morphological evidence of apoptosis, such as pyknotic nuclei, fragmented nuclei, or plasma membrane [PM] blebbing).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since changes in Golgi morphology have been reported to occur during apoptosis (Chiu et al, 2002; Jung et al, 2006; Lane et al, 2002; Mancini et al, 2000; Qian and Yang, 2009), we examined whether DNA-damage-induced Golgi dispersal occurs as a consequence of apoptosis. Although treatment with CPT caused a significant increase in the number of apoptotic cells (Figures 2C and 2D), still only a small fraction of cells became apoptotic (1.74% ± 0.08% [mean ± SEM] positive for cleaved caspase-3 (CCasp-3), coinciding with other morphological evidence of apoptosis, such as pyknotic nuclei, fragmented nuclei, or plasma membrane [PM] blebbing).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of DNA damage on the Golgi has been largely neglected in the literature, with a few prior hints of an effect generally being ascribed to a consequence of DNA-damage-induced apoptosis (Chiu et al, 2002; Jung et al, 2006; Lane et al, 2002; Mancini et al, 2000; Qian and Yang, 2009). The induction of Golgi dispersal by even minimally toxic doses of DNA-damaging agents, the continued apparent health of cells observed by time-lapse microscopy, and the persistence of the Golgi dispersal for weeks all demonstrate that the Golgi response is unrelated to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies as well as others have established the capacity of Adriamycin to promote premature or accelerated senescence in tumor cells (Chang et al, 1999;Elmore et al, 2002;Di et al, 2009;Gewirtz, 2009), whereas a number of studies have indicated that ADR also promotes autophagy Qian and Yang, 2009). We have postulated that both autophagy and senescence may represent efforts by the tumor cell to evade drug or radiation-induced toxicity (Gewirtz, 2009), and it is well established that different modes of cell death may coexist in the same cancer cell population in response to genotoxic stress Jinno-Oue et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, previous studies in thyroid cancer and hepatoma cells have demonstrated that Adriamycin can induce autophagy (Lin et al, 2009;Qian and Yang, 2009). Although senescence and autophagy are generally considered to be two distinct cellular events in response to genotoxic stress, there has been accumulating evidence that the two are functionally intertwined (Gerland et al, 2003;Patschan et al, 2008;Gosselin et al, 2009;Jinno-Oue at al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Lovejoy et al have proposed that since autophagic pathways are abnormal in cancer cells by virtue of monoallelic deletion of the autophagic regulator, beclin1, apoptosis, and cell death would be the favored pathway in cancer cells (156). Doxorubicin also induces autophagy as one of its cellular responses (205). This has been exploited with the autophagy inhibitor, resveratol, to attenuate the cardiotoxic effects of doxorubicin (289).…”
Section: Cellular Responses To Dual Inhibitionmentioning
confidence: 99%